Validation of a semi-quantitative FFQ for 18-month-old toddlers : the Growing Up in Singapore Towards Healthy Outcomes (GUSTO) study - Lim, Hui Xian (2021)
Objective: Dietary intake of toddlers has been of growing interest due to its long-term consequences on health. However, previous works have focused largely on Caucasian populations and less is known about Asian toddlers. We aimed to validate a semi-quantitative FFQ designed to assess dietary intakes of 18-month-old toddlers in a multi-ethnic Asian cohort. Design: An FFQ of ninety-four food items, identified based on food records of 12-month-old GUSTO children, the Southampton Women’s Survey 12 Month Infancy Questionnaire and inputs from paediatric dietitians, was filled out two weeks before the 18th-month clinic visit. As the reference method, two non-consecutive 24 h recalls (24HR) were administered during and two weeks after the clinic visit. FFQ nutrient intakes were validated against averaged 24HR nutrient intakes, using the Wilcoxon signed-rank test, Spearman’s rank-order correlation, cross-classification and the Bland–Altman method. Setting: Data from the Singapore Growing Up in Singapore Towards Healthy Outcomes (GUSTO) mother–offspring birth cohort. Participants: Toddlers (n 188) aged 18 months. Results: Absolute nutrient intakes from the FFQ were significantly higher than from the 24HR, except for vitamin A. After energy adjustments, r range was 0·56–0·78 (macronutrients) and 0·40–0·54 (micronutrients). De-attenuation increased r to 0·58–0·96 and 0·45–0·65 for macro- and micronutrients, respectively. Of participants, ≥82·4 % (macronutrients) and ≥77·7 % (micronutrients) were classified in the same and adjacent quartiles. No clear systematic increase in intake differences with increasing mean intake was observed in Bland–Altman plots. Conclusions: This FFQ can provide a satisfactory assessment of toddlers’ energy-adjusted nutrient intakes, as well as accurately rank them in a group.